A produção de textos na "era Enem" : subjetividade e autoria no contexto político-pedagógico brasileiro contemporâneo - Manso, Guilherme Brambila (2017)
This work brings up results obtained in a Masters research regarding the place of subjectivity and authorship in the writing context of Enem (National High School Examination) evaluation, a national exam applied to Brazilian students in the end of High School in order to enter in most public universities, concomitantly discussing the institutional perspectives regarding language and the writing in contemporaneity. To do so, the research has a documentary analysis of the National Curricular Common Base (hereinafter BNCC), specifically regarding the institutional vision on language in High School and its curricular perspectives towards this place. Dialoging with this analysis, the work also presents a study about subjectivity and authorship in essays that scored 1000 in Enem, in order to ascertain which authors are, in fact, seen as models for the exam system, which is a reality to the Brazilian High School, and whether this panorama is a subject of problematization. The investigation is also proposed to put the BNCC proposals in dialogue with the results obtained from the study of the 1000 graded essays, in order to discuss the ways in which textual practice has taken place in contemporary times. In this way, the work is guided by studies in linguistic policies (RIBEIRO DA SILVA, 2013; AFONSO, 1998), what contribute much to BNCC's analysis; and by the authorship perspective proposed by Bakhtin (1992 [2011]), Barthes (1984) and Foucault (1969), and identity, by Hall (1998), for the analysis of 1000 grade essays. In addition, the work is constantlycrossed by voices of other authors who are engaged in discussions in Applied Linguistics (STREET, 1984, KLEIMAN, 2007, ROJO, 2009, VIDON, 2016, MENDES, 2013, et ali). This study has a qualitative, index-based methodology (GINZBURG, 1986), in which the results are observed in the dialogical plane as components that constantly instigate new problematizations.